MXenes as Emerging 2D Materials for Anticorrosive Application: Challenges and Opportunities. Issue 28 (3rd September 2022) - Verma, Chandrabhan; Zehra, Saman; Aslam, Ruby; Aslam, Jeenat; Quraishi, Mumtaz A.; Mobin, Mohammad
Abstract: MXenes (MXs) (singular; "MXene" (MX); pronounced "Maxenes") are a relatively new class of 2D inorganic materials that possess numerous potential biological and industrial applications. After the discovery of the first MXene, Ti3 C2 T x, in 2011 plenty of reports on the synthesis and application of MXenes and their derivatives are published in the literature. Generally, MXenes contain heteroatoms at their surface; therefore, they can act as strong ligands and can form coordination bonding with the metal atoms and their ions. Because of this property, recently MXenes are used as nanofillers in polymer‐based coatings. The MXenes possess excellent filler properties. They are extensively used as fillers in epoxy resins and polyurethane‐based coatings but their application as fillers in other polymers is highly limited, which opens an area to explore in the future. The anticorrosive application of MXenes‐filled polymers coatings is extensively reported. The contemporary review designates the assemblies of various reports on the anticorrosive and filler property of the MXenes and their composites. Previous studies suggest that MXenes and their composites not only affect the performance of polymer coatings but also enhance their durability. The present report also describes the synthesis, characterization, chemical structures, and properties of the MXenes and their composites. Abstract : MXenes are a quite novel class of 2D inorganic materials that have many possible industrial and biological applications. The review paper describes the synthesis, characterization, and current advancements in using MXenes and their derivatives for anticorrosive application. The review also focuses on challenges and future prospective.